Correlation of Blood culture with C-Reactive Protein , WBC count in the diagnoses of Bacterial Neonatal Sepsis - R Bharathi; PM , Beena; K, Mamata; S, Parimala (Tropical Journal of Pathology and Microbiology, 2021)
Abstract Introduction The diagnosis of sepsis in neonates is challenging. C- reactive protein (CRP), White blood cell counts are the widely used biomarkers in neonatal sepsis screening by clinicians. Aim To assess the value of C-reactive protein alone and in combination with total White Blood Cell (WBC) count in screening of neonatal sepsis. Materials and Methods A retrospective study was conducted from March to November 2018 at R L Jalappa Hospital& Research centre , Kolar, Karnataka, India. Data was analysed using SPSS version 22.0 statistical software for further analysis. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were used the accuracy of CRP and WBC taking blood culture as gold standard. Results Data of 127 neonates with clinical neonatal sepsis were analysed. Blood culture was positive in 28 (22.04 % ) neonates. CRP was positive in 20 (71.42% ) blood culture positive cases. Out of 99 culture negative cases , WBC changes were noted with 30 (30.30%) of cases . The sensitivity , specificity of CRP were 71.4%, 69.9% respectively with positive predictive value (PPV) of 36.6% and negative predictive value(NPV) 88.89%. On the another hand, sensitivity and specificity of WBC were 21.43% and 78.79% with PPV and NPV of 22.22% and 78.5% respectively. When positive CRP was combined with total WBC count the sensitivity and specificity was raised to 78.57% and 81.81% respectively. Conclusion In resource limited settings for blood cultures , the positive CRP assay in combination with raised WBC counts in neonates with clinical features of sepsis should be considered for immediate management of neonatal sepsis to reduce the morbidity and mortality. Key Words : Neonatal sepsis, CRP,